Review Study on Health and Wellness Tourism - Utama, I Gusti Bagus Rai; Sukmana, IWK. Teja (Technium Social Sciences Journal, 2021)
The need for health and wellness is not new but has existed since humans have known the world of traditional medicine. Ancient people might wander to get medicinal ingredients in the form of plants or herbs to increase fitness and maybe also to treat certain diseases. Spices and the like are one type of commodity that has always been a necessity to meet health and wellness needs. During routine and busyness, humans try to get out of routine by traveling to get health and fitness, both carried out in their own country or across countries. For modern society, health therapy as well as means to pamper oneself have become a necessity and have even become a trend currently, including subscriptions to come for Spa or therapy to recover the body from fatigue into a lifestyle of the community and is growing rapidly.